2019
DOI: 10.1158/1078-0432.ccr-18-2258
|View full text |Cite
|
Sign up to set email alerts
|

E3611—A Randomized Phase II Study of Ipilimumab at 3 or 10 mg/kg Alone or in Combination with High-Dose Interferon-α2b in Advanced Melanoma

Abstract: Purpose: Interferon-a favors a Th1 shift in immunity, and combining with ipilimumab (ipi) at 3 or 10 mg/kg may downregulate CTLA4-mediated suppressive effects, leading to more durable antitumor immune responses. A study of tremelimumab and high-dose interferon-a (HDI) showed promising efficacy, supporting this hypothesis. Patients and Methods: E3611 followed a 2-by-2 factorial design (A: ipi10þHDI; B: ipi10; C: ipi3þHDI; D: ipi3) to evaluate (i) no HDI versus HDI (across ipilimumab doses) and (ii) ipi3 versus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(39 reference statements)
0
5
1
Order By: Relevance
“…A recent phase II study in patients who received at least one previous treatment reported a nonstatistical dose effect on progression-free survival (PFS), but not OS. 18 In contrast, results from the study presented here showed a significant improvement in OS, but not PFS, with 10 mg/kg vs 3 mg/kg. 11 Taking these results together, further investigation is needed to answer the important question of potential ipilimumab efficacy and dose-dependency.…”
Section: Open Accesscontrasting
confidence: 76%
“…A recent phase II study in patients who received at least one previous treatment reported a nonstatistical dose effect on progression-free survival (PFS), but not OS. 18 In contrast, results from the study presented here showed a significant improvement in OS, but not PFS, with 10 mg/kg vs 3 mg/kg. 11 Taking these results together, further investigation is needed to answer the important question of potential ipilimumab efficacy and dose-dependency.…”
Section: Open Accesscontrasting
confidence: 76%
“…In addition, 38 clinical trials with results from https://ClinicalTrials.gov were identified and included. Overall, we included a total of 160 clinical trials involving 40 432 patients in the meta‐analysis (Figure , Table ) . The trials include 37 phase 3 studies with 25 084 patients; 1 phase 2/3 study with 1033 patients; 66 phase 2 studies with 8529 patients; 11 phase 1/2 studies with 1263 patients; and 45 phase 1 studies with 4523 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the median overall survival of patients who received combination therapy was lower at 20.1 months (95% CI, 8.5‐33.6 months). In comparison, those who received ipilimumab alone reported median overall survival of 24.7 months (95% CI, 12.6‐35.7 months) . Although the data did not reach statistical significance, the modest improvement in clinical outcomes are in support of combination therapy of ipilimumab and recombinant IFNα‐2b.…”
Section: Roles Of Ifnα In Cancer Immunoeditingmentioning
confidence: 93%